Modeling of Ventilation’s Influence on Energy Consumption in Multi-cylinder Dryer Section Part 2: Simulations and Applications - Yongjun Yin; Jingjing Yang; Yanlong Jia; Shuang Lan; Zhaoli Liao (International Journal of Computational Intelligence Systems, 2022)
Abstract Ventilation system affects the water evaporation rate, energy consumption and the paper quality, which is considered as the largest optimization potential part of multi-cylinder dryer section. In this paper, energy consumption models of multi-cylinder dryer section are constructed by combining energy modules of moisture evaporation, heat recovery system, air heaters, supply air and exhaust air. Taking a corrugated paper machine as an example, ventilation system influence on the energy consumption of drying system is analyzed systematically. It is concluded that reducing the temperature of supply air and increasing exhaust humidity as much as possible to save energy consumption on the premise of meeting the safety production. The increase of supply air humidity will lead to the increase of steam consumption for heating supply air, power consumption of fans, and the total steam consumption in the drying process, so the intake point of supply air should be chosen at the point with low absolute humidity. The models can predict the energy consumption of ventilation system adjustment and optimization, and provide a method for energy-saving evaluation of ventilation system technical transformation in drying process.